Gastrodiplomacy as a Cultural Soft Power Strategy: Exploring Indonesian MSME Entrepreneurs’ Perspectives and Vocational Skill Development Needs - Maosul, Asep; Syaom Barliana, Mokhamad; Ana, A; Subekti, Sri; Yulia Rahmawati; Setiawati, Tati (Journal of Technical Education and Training, 2026)
This study investigates Indonesian Micro, Small, and Medium Enterprise (MSME) entrepreneurs’ perceptions of gastrodiplomacy as a cultural soft power strategy and identifies vocational skill development needs to enhance their participation in culinary cultural diplomacy. Despite Indonesia’s rich culinary heritage, limited awareness and capacity constraints hinder MSMEs from leveraging gastrodiplomacy to penetrate international markets. Employing a mixed-methods approach with 22 culinary MSME entrepreneurs in Garut Regency, West Java, this preliminary study utilized structured questionnaires and semi-structured interviews analyzed through descriptive statistics and thematic analysis. Findings reveal a paradox: while only 31.8% of respondents were familiar with gastrodiplomacy concepts, 77.3% expressed strong interest in learning, and 100% recognized the need for specialized vocational training. Despite low conceptual awareness, 54.5% already engaged in intuitive cultural promotion activities through social media and local collaborations. Key barriers include complex export regulations (68.2%), limited market information (63.6%), and high costs (59.1%). Comparative analysis with successful gastrodiplomacy programs in Thailand ("Kitchen of the World") and South Korea ("Hansik Globalization") highlights the potential for Indonesia to systematically leverage its culinary diversity. The study proposes a comprehensive vocational skill model integrating gastrodiplomacy theory, digital marketing competencies, export navigation, and cultural branding strategies. These findings provide empirical foundation for policy interventions supporting MSME capacity building in gastrodiplomacy, contributing to national soft power enhancement and sustainable economic development through cultural diplomacy.